Analysis of Service Quality Level of Financing in Bank BTN Syariah Using the Fuzzy SERVQUAL Method (Case Study: Financing Unit of Bank BTN Syariah Balikpapan Branch) - Pambudi, Rifky; Safar Tosungku, La Ode Ahmad; Amelia Pawitra, Theresia (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Bank Tabungan Negara (BTN) Balikpapan is a financial institution that collects funds from the public and channels them in the form of credit. The objective of this research is to measure the service quality at Bank BTN Syariah Balikpapan using the SERVQUAL, conduct an analysis using the Fuzzy method to obtain single values that represent each attribute of perceptions and expectations, and formulate improvement proposals to enhance the quality of financing services. The highest gap was found in attribute Q1